Users’ emotional evaluation towards kansei-based higher learning institution website using geneva emotion wheel - Punitha Turumugon; Aslina Baharum; Nadia Hanin Nazlan; Nor Azida Mohamed Noh; Noorsidi Aizuddin Mat Noor; Emelia Abdul Rahim (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Functionality, usability, and pleasure are the three elements that influence consumers decision-making and behavioral intentions. This study attempts to fill in the gap in the web design literature by justifying the Kansei-based engineering technique by embedding emotional cues in Higher Learning website designs. This study aims to test the effectiveness of a Kansei-based website that was designed in accordance with the Kansei-based standards for web design. Using an online Geneva Emotion Wheel survey, the results suggest that the Kansei-based website elicit favorable positive emotion from users